Modelling the relationships between EEG signals, movement kinematics and outcome in soccer kicking - Palucci Vieira, Luiz H. [UNESP]; Carling, Christopher; da Silva, João Pedro [UNESP]; Santinelli, Felipe B. [UNESP]; Polastri, Paula F. [UNESP]; Santiago, Paulo R. P.; Barbieri, Fabio A. [UNESP] (Springer Nature, 2022)
The contribution of cortical activity (e.g. EEG recordings) in various brain regions to motor control during goal-directed manipulative tasks using lower limbs remains unexplored. Therefore, the aim of the current study was to determine the magnitude of associations between EEG-derived brain activity and soccer kicking parameters. Twenty-four under-17 players performed an instep kicking task (18 m from the goal) aiming to hit 1 × 1 m targets allocated in the goalpost upper corners in the presence of a goalkeeper. Using a portable 64-channel EEG system, brain oscillations in delta, theta, alpha, beta and gamma frequency bands were determined at the frontal, motor, parietal and occipital regions separately for three phases of the kicks: preparatory, approach and immediately prior to ball contact. Movement kinematic measures included segmental linear and relative velocities, angular joint displacement and velocities. Mean radial error and ball velocity were assumed as outcome indicators. A significant influence of frontal theta power immediately prior to ball contact was observed in the variance of ball velocity (R2 = 35%, P = 0.01) while the expression of occipital alpha component recorded during the preparatory phase contributed to the mean radial error (R2 = 20%, P = 0.049). Ankle eversion angle at impact moment likely mediated the association between frontal theta power and subsequent ball velocity (β = 0.151, P = 0.06). The present analysis showed that the brain signalling at cortical level may be determinant in movement control, ball velocity and accuracy when performing kick attempts from the edge of penalty area. Trial registration number #RBR-8prx2m—Brazilian Registry of Clinical Trials ReBec.
Keywords: 3-dimensional analysis; Accuracy; Motor control; Neuropsychophysiology; Prediction; Team sports